The genetics of diabetes mellitus - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
It is now clear that diabetes mellitus is not a disease in classical sense but is a genetically heterogeneous group of disorders which share glucose intolerance in common. Genetic heterogeneity, the concept that diabetes can have many different causes, was first suggested by the existence of rare genetic syndromes with diabetes, ethnic differences of clinical features, and genetic heterogeneity in animal models.This paper describes the background for genetic heterogeneity of diabetes mellitus which has major implications for the research and care of diabetic patients since the precise etiology, risk of complications and genetic counselling are likely to vary among these different disorder that result in diabetes.Key Words: diabetes mellitus - genetic heterogeneity - mode of inheritance - genetic counselling - antoinunune process